A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae) - Enghoff, Henrik; Jensen, Laura Mark; Mikhaljova, Elena V. (European Journal of Taxonomy, 2017)
The genus Koiulus gen. nov. and its type-species, Koiulus interruptus gen. et sp. nov., are described from the Russian Far East. The new genus is compared with other genera of Mongoliulidae, in particular with Ussuriiulus Golovatch, 1980, also from the Russian Far East, with which it shares the absence of ozopores from individual body rings distributed along the body, a condition so far otherwise unknown in the superorder Juliformia. A synoptic table of genera and a list of species of Mongoliulidae are presented.